Pengaruh Cyberloafing Dan Komitmen Organisasional Terhadap Kinerja Pegawai Dengan Self Control Sebagai Variabel Moderating - Catarina Cori Paramitha; Ira Wahyuni (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to test and analyze the effect of cyberloafing and organizational commitment on employee performance with self-control as the moderating variable. The population in this study used a sample of 186 respondents, who are employees of private companies in Jakarta. The data collection technique uses simple random sampling by distributing google form questionnaires and spreading it to social media such as Whatsapp and Instagram. The data processing method in this study uses Smart PLS3 software which is used to test the hypothesis. The method of determining the number of respondents (eligibility) can use Hair. The results of this study indicate that the effect of cyberlofing has a negative effect on employee performance, organizational commitment cannot be a factor in employee performance, changes in self-control have a positive or significant effect on employee performance, moderation in cyberloafing behavior changes can weaken and negatively affect self control on employee performance, change moderation. self control is able to strengthen and significantly influence organizational commitment on employee performance.Keywords: Cyberloafing, Organizational Commitment, Employee Performance, Self Control